An innovative and simple approach to fabricate a hollow ocular prosthesis with functional lubricant reservoir: A solution to artificial eye comfort - Aditya Anil Kavlekar; Meena Ajay Aras; Vidya Chitre (Wolters Kluwer Medknow Publications, 2017)
The loss of an eye is an emotional and psychological setback to the patient. An ocular prosthesis is created to restore the lost anatomical structure and to correct the cosmetic defect. The tear reflexes do not function at optimal levels in anophthalmic sockets which make prosthesis wear uncomfortable. This case report presents an innovative hollow ocular prosthesis with functional lubricant reservoir which upon normal blinking would draw the lubricant from the reservoir through an exit hole which spreads over the prosthesis allowing a comfortable and long duration of prosthesis wear.